Online labour markets - levelling the playing field for international service markets? - Lehdonvirta, V; Barnard, H; Graham, M; Hjorth, I (Oxford Internet Institute, 2014)
The Internet has long been predicted to become a shortcut that allows workers to work for any employer regardless of their location. To some extent this has now become a reality, with the rise of “online labour markets” that bring together buyers and sellers of intangible knowledge and service work from around the world. Practical considerations such as language and time zone differences can be expected to shape those markets, but a long tradition of research in international business finds that foreignness per se can also be a liability. In this paper, we use data from the largest global online marketplace to examine the degree to which geography still matters, not just for practical matters but also in terms of a persisting perception of foreignness in the online space. We find that the market is highly international, with most employers residing in rich countries and most workers in poor countries. However, workers are more likely to find work in their domestic markets. Moreover, domestic contractors get paid more than international contractors for the same type of work. Our analysis suggests that this bias against international contractors is not only due to practical factors such as time zone differences and language-based communication difficulties, but especially to what can be termed a “liability of foreignness”. We conclude that while the Internet can bridge physical distance, there are also other geographically conditioned barriers to trade that digital connectivity doesn’t necessarily address.